Modeling the transport and bioreduction of hexavalent chromium in aquifers: Influence of natural organic matter. (22nd December 2015) - Thacher, Ryan; Hsu, Lewis; Ravindran, Varadarajan; Nealson, Kenneth H.; Pirbazari, Massoud
Abstract: Hexavalent chromium (Cr VI ) is a carcinogenic heavy metal that is a product of many industrial processes and an important contaminant in aquifers. The study investigates alternative remediation options for Cr VI through the integration of effective contaminant transport and microbial biofilms. Bioactive sand reactor studies were conducted using columns charged with Shewanella oneidensis MR-1 biofilm growth in sand media. A biofilm reactor dynamics model was employed to predict Cr VI reduction in bioactive sand columns from the standpoint of aquifer remediation and water treatment. The model utilized biokinetic parameters determined from independent microbial batch reactor studies using the Monod model. The biokinetic and reactor dynamics models further demonstrated that humic acid acted as electron shuttle and electron acceptor with lactate as electron donor, enhancing biological activity and Cr VI reduction. The reactor model accurately forecast process dynamics for both scenarios with and without humic acid. Model sensitivity studies provided additional insight into the influence of various parameters on system dynamics and the means for improving process efficiencies. Highlights: Bioactive sand column reactors yield high removals of hexavalent chromium. Shewanella MR-1 effective for hexavalent chromium reduction in simulated aquifers. Natural organic matter such as humic acid enhance hexavalent chromium removals. Model accurately predicts hexavalent chromium removals in aquifers and reactors. Model simulations offer insight into process variables affecting reactor dynamics.